Airline Business Models and their respective carbon footprint: Final report - Mason, Keith J.; Miyoshi, Chikage (Manchester Metropolitan University, 2009)
The choices that airlines make about the aircraft they fly, the number of seats they have on each aircraft, the routes they fly and the passenger segments they focus on have significant impacts on their environmental performance (which can be assessed in terms of an airline’s CO2 emissions per passenger kilometre, fuel burn or other suitable metric). Each of the main airline business models (network, charter, low cost carrier (LCC), regional) involves practices that may improve or degrade environmental performance. This project analyses the factors that affect each business model’s environmental performance and considers the potential for changes to business models to improve the environmental sustainability of the aviation sector. The evolution of aircraft fuel consumption, average sector length and CO2 emission levels (per passenger kilometre) were investigated. From 1986 to 2004 total fuel consumed by European airlines1 increased by 220%, while the amount of fuel consumed per passenger km has decreased by 27% (or 2% per year). Average distance flown has increased by 21% and the average number of passengers carried per flight by 5%. The CO2 emissions of intra-EU air services from the UK generated by each business model (network, LCC, charter, regional) was established for the years 1997, 2000 and 2006. Emissions were estimated by route, stage length, aircraft type used, number of seats supplied on each aircraft and the distance flown, following the IPCC recommended approach to carbon dioxide calculation. The LCCs share of total emissions has risen to 46% of all intra-EU routes originating in the UK in 2006 from 12% in 1997. At 112g/pkm this group’s CO2 emissions are lower than either network carriers or regional airlines (at 144g/pkms and 216g/pkms respectively) in the EU market. However the lowest emissions level is achieved by charter airlines at 106g/pkm. Some activities airlines have undertaken to reduce on-board weight were also considered. These include reducing water carriage, lowering tankered fuel levels and re-designing the duty free sales process. A calculator that estimates the carbon dioxide emissions that can be prevented by removing weight from a number of aircraft types was developed. It estimates that 456.2 tonnes of CO2 emissions can be prevented if an airline operating a daily North Atlantic service with a Boeing 747-400 could reduce 1 tonne (metric) from its takeoff weight. One of the main policy instruments that can internalise the environmental costs of aviation is the European Emissions Trading Scheme. Prior to its introduction the UK government has increased its Air Passenger Duty as a quasi-environmental taxation measure. The success of such fiscal measures in dampening the demand for air transport will largely depend on the price elasticity of demand and indicative ranges for long and short haul leisure and business passengers are given. A model of air transport CO2 emissions, which was developed to test various scenarios, suggests that should current growth rates continue, emissions for the global aviation market may grow by over 50% between 2009 and 2020. With high growth rates, the share of emissions for low cost carriers would also grow significantly, however, it is also clear that network carrier’s growth of long haul flying also means that the absolute emissions levels of this group is also likely to rise. The output of the model is used to test the sensitivity of changes to business model, such as increasing load factors, increasing the number of seats on board an aircraft, and differing growth rates for each business model. A stakeholder workshop and seminar for this project and a sister Omega project “Passenger Expectations” was held in December 2008. Key outcomes of the seminar was that passengers seem to have little appetite for changes in behaviour (such as willingness to take fewer longer overseas holidays or to holiday within the UK) that might reduce the demand for air services and that further passenger education regarding the relative impact of flying compared to other GHG generating activities is required. Further research is required to assess passenger willingness to forego service levels, timetable frequency, flight times to maximise load factors, minimise aircraft weight and therefore fuel consumption. Future studies may extend this work in two ways: assessing the feasibility of fully adopting the various weight reduction strategies suggested for airlines; and by investigating network carriers’ freight operations as a source of carbon dioxide emissions. Keith Mason and Chikage Miyoshi Cranfield University March 2009